Pengaruh Promosi Dan Harga Terhadap Perilaku Pembelian Impulsif Produk Skincare Dan Makeup Pada Toko Kesehatan Dan Kecantikan Olive Young Di Busan Korea Selatan - Nur Wafani, Alya Nike (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of promotion and price on impulsive buying behavior of skincare and makeup products at Olive Young, a leading health and beauty store in Busan, South Korea. Impulsive buying is a frequent phenomenon in the beauty retail sector, particularly among international students who face financial limitations yet remain highly responsive to various marketing strategies. This research employed a quantitative approach with a survey method by distributing questionnaires to 100 respondents, namely international students at Youngsan University who had shopped at Olive Young Busan. Data analysis was conducted using validity and reliability tests, multiple regression analysis, and mediation tests. The findings reveal that promotion has a positive and significant effect on impulsive buying behavior. Price also demonstrates a positive and significant influence, as competitive pricing, discounts, and bundling offers trigger spontaneous purchasing decisions. Simultaneously, promotion and price significantly affect impulsive buying behavior with a substantial contribution, although other factors beyond this study also play a role. These results highlight that effective promotional strategies and appropriate pricing are key drivers of impulsive buying in the beauty retail sector. This study is expected to provide both theoretical and practical contributions, particularly for retail businesses in designing more effective marketing strategies to attract international consumers.